Cryosensitivity of Mesenchymal Stromal Cells Cryopreserved Within Marine Sponge Ianthella basta Skeleton-Based Carriers - Mutsenko, Vitaliy V.; Rogulska, Olena Yu.; Petrenko, Yuriy A.; Ehrlich, Hermann; Mazur, Svetlana P.; Volkova, Natalya A.; Petrenko, Aleksandr Yu. (Problems of Cryobiology and Cryomedicine, 2016)
This paper presents our findings on using skeletons of marine sponge Ianthella basta as the carriers for human mesenchymal stromal cells (MSC), evaluating their biocompatibility with the cells, as well as the assessment of cryosensitivity of the cells, growing within these carriers to cryopreservation under protection of 10% DMSO and 20% fetal bovine serum according to the method developed for MSC suspension (slow cooling with 1 deg/min rate, rapid thawing at 37Â°Ð¡). Network-like chitin carriers consisting of chitin fibrils were derived from marine sponge Ianthella basta skeletons by acid-base hydrolysis. During culturing in vitro these carriers supported adhesion, migration and proliferation of MSCs. After cryopreservation we observed a decrease in cell viability with their metabolic activity of 46.8Â±5.8% in respect to the native specimens and it did not reduce to day 1 of reculture. As proceeded from the reported findings, the skeletons from marine sponge Ianthella basta are the new promising source for carriers to be used in tissue engineering and regenerative medicine. This research may serve the basis for further developing the cryopreservation methods for stem cells within 3-D tissue-engineered scaffolds. Â Probl Cryobiol Cryomed 2016; 26(1):13-23.